The effects of sex, metabolic syndrome and exercise on postprandial lipemia - Cox-York, Kimberly A. (2012)
OBJECTIVE: Exercise has been suggested to have cardio protective benefits due to a lowering of postprandial triglycerides (PPTG). We hypothesized that a morning exercise bout would significantly lower PPTG measured over a full day, in response to moderate fat meals (35% energy) in men more so than women, and in metabolic syndrome (MetS) relative to normal weight (NW) individuals. MATERIALS/METHODS: Participants completed two randomized study days; one control and one exercise day (60 min of morning exercise, 60% VO(2)peak). Meals were consumed at breakfast, lunch and dinner with the energy expended during exercise replaced on the active day. The areas (AUC) and incremental areas (IAUC) under the curve were calculated for total triglycerides, total cholesterol and other metabolites. RESULTS: Exercise did not significantly change the PPTG AUC & IAUC overall, nor within, or between, each sex or group (NW and MetS). Exercise induced a 30% decrease in total cholesterol IAUC (p = 0.003) in NW subjects. Overall, women had a lower IAUC for PPTG compared to men (p = 0.037), with the greatest difference between MetS women and MetS men, due to a sustained drop in TG after lunch in the women. This suggests that PP, rather than fasting, lipid analyses may be particularly important when evaluating sex differences in metabolic risk. CONCLUSIONS: With energy replacement, moderate morning exercise did not result in a significant decrease in PPTG excursions. Exercise did elicit a significant decrease in PP cholesterol levels in NW subjects, suggesting a potential mechanism for the cardio protective effects of exercise.